1995
DOI: 10.1177/43.1.7822764
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization of parathyroid hormone-related protein in normal skin, skin tumors, and gynecological cancers using digoxigenin-labeled probes and antibody enhancement.

Abstract: We describe a novel procedure for in situ hybridization that combines the use of digoxigenin-labeled oligonucleotide probes with an antibody enhancement step that can be performed on formalin-fixed, paraffin-embedded tissues. Addition of a second antibody enhances the visibility of parathyroid hormone-related protein (PTHrP) mRNA expression from barely to highly discernible and interpretable, with virtually no nonspecific background expression. This technique has allowed visualization of PTHrP mRNA in normal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
0
19
0
2
Order By: Relevance
“…These include CCL20 (MIP3), a strong chemoattractant for Langerhans cells (47); CXCL12, which affects T cells; and vascular epidermal growth factor, which plays a role in angiogenesis, cancer, and wound healing (48). In contrast, PTHLH, whose expression is specific for basal cells, is suppressed by SP600125 (49).…”
Section: Table 2 Over-represented Binding Sites For Transcription Facmentioning
confidence: 99%
“…These include CCL20 (MIP3), a strong chemoattractant for Langerhans cells (47); CXCL12, which affects T cells; and vascular epidermal growth factor, which plays a role in angiogenesis, cancer, and wound healing (48). In contrast, PTHLH, whose expression is specific for basal cells, is suppressed by SP600125 (49).…”
Section: Table 2 Over-represented Binding Sites For Transcription Facmentioning
confidence: 99%
“…However, this receptor responds to PTH and PTHrP differently from the conventional PTHR1 receptor—normal keratinocytes do not express their gene for the conventional PTHR1 although some might do so during “immortalization” [Henderson et al, 1992; Hanafin et al, 1995; Orloff et al, 1995; Sharpe et al, 1998] And this receptor, whatever it may be, does not couple to adenylyl cyclase, although the keratinocytes have the machinery to do so because they can respond to the β‐adrenergic receptor‐activating isoproterenol with a large burst of adenylyl cyclase activity [Whitfield et al, 1992; Orloff et al, 1995]. Moreover, keratinocytes can be made to respond to PTH‐(1‐34) with a burst of adenylyl cyclase activity if they are engineered to express the conventional PTHR1 receptor [Orloff et al, 1995] However, the TA keratinocytes do not start making the PTHrP to stimulate these unconventional PTH receptors until they have stopped proliferating and lifted off the basal lamina [Juhlin et al, 1992; Danks et al, 1995; reviewed by Whitfield and Chakravarthy, 2001] (Fig. 3).…”
Section: A Different Use For Pths—treating Psoriasismentioning
confidence: 99%
“…And this is could well be the reason for the hyperproliferation because Nicolas et al [2003] have shown that eliminating Notch 1 in mice causes epidermal hyperplasia through a proliferogenic upregulation of β‐catenin and Gli2 expression. And along with these striking differences they don't make PTHrP [Juhlin et al, 1992], probably because of the breakdown of the Notch/Notch ligands mechanism that would normally have restrained β‐catenin and Gli2 expression and driven the stem cell ⇒ TA cell transition, with the resulting stratification, generation of the Ca 2+ gradient and PTHrP expression in the spinous and granular layers [Juhlin et al, 1992; Danks et al, 1995; Lowell et al, 2000; Whitfield and Chakravarthy, 2001; Thélu et al, 2002].…”
Section: A Different Use For Pths—treating Psoriasismentioning
confidence: 99%
“…Parathyroid hormone-related protein has been loca¬ lized by immunohistochemistry in normal skin to basal and spinous keratinocytes (8,9,47,48), and is present consistently in SCCs (8,9,48). However, when these data were adjusted for DNA content, PTHrP secretion decreased with increased DNA content.…”
Section: Discussionmentioning
confidence: 99%